Moringa seed extract inhibits the growth of Candida albicans - Ali Yusran; Exsa Sasmita Malan (Makassar Dental Journal, 2020)
Background: Candida albicans are normal flora in the oral cavity and can turn into pathogens. Antifungal drugs need to be given to inhibit the growth of the fungus; using traditional medicine, for example moringa seeds. Moringa seeds contain natural compounds like polyphenols and flavonoids as an antifungal.Objective: To determine the inhibition of Moringa oleifera L. seed extract on the growth of C.albicans. Method: This experimental laboratory research was designed with posttest only control group with agar/Kirby Bauer diffusion method, carried out with 4 repetitions by treated extract with 40%, 60%, 80%, 100% concentration, positive control (ketoconazole) and negative controls (distilled water). Results: Krusskal Wallis test showed p value = 0.000 (p <0.05),means Moringa seed extract with concentrations 40%, 60%, 80%, 100% had a significant effect on inhibiting the growth of C.albicans. Conclusion: Moringa seed extract can inhibit the growth of Candida albicans.